2022
DOI: 10.3389/fonc.2022.905520
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic targeting of VEGF and/or TGF-β to enhance anti-PD-(L)1 therapy: The evidence from clinical trials

Abstract: Normalizing the tumor microenvironment (TME) is a potential strategy to improve the effectiveness of immunotherapy. Vascular endothelial growth factor (VEGF) and transforming growth factor (TGF)-β pathways play an important role in the development and function of the TME, contributing to the immunosuppressive status of TME. To inhibit VEGF and/or TGF-β pathways can restore TME from immunosuppressive to immune-supportive status and enhance sensitivity to immunotherapy such as programmed death protein-1 (PD-1)/p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 112 publications
(171 reference statements)
0
4
0
Order By: Relevance
“…As a cell proliferation marker, Ki67 expression is closely related to tumor growth, invasion and metastasis ( 23 ). VEGF is a cytokine expressed in vascular endothelial cells to promote angiogenesis ( 24 ). CD31 participates in cell adhesion and regulates angiogenesis, it can be used to estimate the number of MVDs and as a “gold standard” reflecting the number of neovascularizations ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…As a cell proliferation marker, Ki67 expression is closely related to tumor growth, invasion and metastasis ( 23 ). VEGF is a cytokine expressed in vascular endothelial cells to promote angiogenesis ( 24 ). CD31 participates in cell adhesion and regulates angiogenesis, it can be used to estimate the number of MVDs and as a “gold standard” reflecting the number of neovascularizations ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that many of these AGFs can be the important causes of immunosuppression in the glioma microenvironment. Combination of anti-angiogenic drugs and immunotherapy has become one of the standard therapeutic regimens for multiple cancers ( 8 10 ). At present, the role of AGFs and their corresponding receptors in glioma immune microenvironment have not been comprehensively studied.…”
Section: Concluding Remarks and Perspectivesmentioning
confidence: 99%
“…Anti-angiogenic therapy by targeting AGFs to normalize tumor vessels has also been found to improve anti-tumor immunity. Combination of anti-angiogenic drugs and immunotherapy has become a canonical treatment for hepatocellular carcinoma, non-small cell lung cancer and renal cell carcinoma, but still, it has not always been successful ( 8 10 ). A better understanding of the tangled interplay among AGFs, immune cells and cancer cells in the TME is urgently needed to shed lights on finding new anti-tumor therapeutic avenues.…”
Section: Introductionmentioning
confidence: 99%
“…Two subtypes of M2-like macrophages, M2c and M2d, are responsible for producing TGFB ligands that maintain the TME in an immunosuppressive state [ 23 , 24 ]. These subtypes of M2 macrophages also regulate the expression of extracellular matrix proteins, which augment tumor migration and invasion [ 25 , 26 , 27 ]. One study found that TGFB2, through MMP-2 expression, supported tumor cell invasion by breaking down the basal membrane [ 28 ].…”
Section: Introductionmentioning
confidence: 99%